2013
DOI: 10.1371/journal.pone.0054374
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces Apoptosis in Pancreatic β-Cells through a Mitochondria-Dependent Pathway: The Role of Oxidative Stress-Mediated c-Jun N-Terminal Kinase Activation

Abstract: Cadmium (Cd), one of well-known highly toxic environmental and industrial pollutants, causes a number of adverse health effects and diseases in humans. The growing epidemiological studies have suggested a possible link between Cd exposure and diabetes mellitus (DM). However, the toxicological effects and underlying mechanisms of Cd-induced pancreatic β-cell injury are still unknown. In this study, we found that Cd significantly decreased cell viability, and increased sub-G1 hypodiploid cells and annexin V-Cy3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 43 publications
4
73
0
Order By: Relevance
“…Similar results were observed by (Chang et al, 2013) and they observed that cadmium also increased intracellular reactive oxygen species (ROS) generation and malondialdehyde (MDA) production and induced mitochondrial dysfunction in pancreatic β-cells.…”
supporting
confidence: 79%
“…Similar results were observed by (Chang et al, 2013) and they observed that cadmium also increased intracellular reactive oxygen species (ROS) generation and malondialdehyde (MDA) production and induced mitochondrial dysfunction in pancreatic β-cells.…”
supporting
confidence: 79%
“…This finding appeared from both microscopic examinations of immunohistologically stained sections and AI calculation. The apoptotic effect of Cd was reported by different authors on pituitary gland [32,33] and other tissues [34][35][36].…”
Section: Discussionmentioning
confidence: 75%
“…A deterioration of β cell function may happen once a certain toxic cadmium level is exceeded. It has also been found that cadmium may induce hyperglycemia, alter lipid metabolism (Trevino et al 2015) and induce apoptosis in pancreatic β cells (Chang et al 2013). One previous study observed a reduction of serum insulin level in cadmium exposure rats (Edwards and Prozialeck 2009).…”
Section: Discussionmentioning
confidence: 99%